Design fabrication and performance analysis of length morphing rotor blade - Saravanan, G; Kumar Annamalai, Vinoth; Bharath, N; Kevin, Antonio; Rahul Teja, G; Steven Anto, Neil (International Journal of Engineering and Technology, 2018)
The present work deals with helicopter theory involving the study, design and fabrication of the helicopter rotor blades with the length-morphing mechanism. The research of the rotor blades has enabled in a proper understanding of the aerodynamics and design of the same. The thrust produced by a blade is proportional to its area, and for every motor RPM, maximum thrust efficiency is achieved for a discrete length of the rotor blade. Facing this complexity, designers compute an optimal length for the average motor RPM while designing the heli-copter blades. Acknowledging the challenges, Length-Morphing rotor blades targeting maximum thrust efficiency for each motor RPM was developed with the aid of knowledge in Blade Element Theory. The rotor blade was designed and fabricated to be driven by the centrifugal force from the motor. The rotor blade was divided into fixed inboard section and sliding outboard part in a span-wise direction. The analy-sis was carried out to study and comprehend the operating conditions of the length-variable rotor during revolutions and to derive the design variables of extension-spring and rotor weight. Variation of thrust concerning the length of the rotor blade was studied, and the setup was fabricated. The project aims to enable maximum rotor blade thrust efficiency for each RPM of the motor by varying the length of the rotor blade and computing the performance characteristics of the same.Â Â